Sex Differences in Ischemic Stroke Within the Younger Age Group: A Register-Based Study - Norman, Kristina; Eriksson, Marie; von Euler, Mia (Frontiers in Neurology, 2022)
Background: Stroke incidence is decreasing in most developing countries. However, worrisome trends of an increase in the younger population have been described. Sex is an important factor in stroke and while it is known that women are older at onset and stroke is more common among men under 75 years, sex differences in the younger age group are less studied. Aim: To investigate sex differences in ischemic stroke regarding incidence, risk factors and case fatality, in the young. Methods: This is an observational study based on data from the Swedish national stroke registry, Riksstroke. Patients who met the inclusion criteria of being 18-54 years of age and having an ischemic stroke between 2005-2018 were extracted from Riksstroke, resulting in a study population of 16,210 patients. The patients were analyzed and compared to the Swedish population regarding incidence, risk factors and 90-days case fatality. Results: More men than women were affected (62.5% and 37.5%, respectively). Atrial fibrillation, diabetes and usage of anti-hypertensives was significantly more common among men, while smoking, previous stroke and 90-days case fatality showed no sex differences. Incidence rates per 100,000 person-years did not illustrate any clear temporal trends. Conclusions: The results show that there are sex differences in ischemic stroke in the younger age group regarding incidence and vascular risk factors, and these differences increase with age. Temporal trends in stroke incidence rates are difficult to predict as fluctuations are substantial, largely due to stroke being quite uncommon in the younger population.